An Empirical Analysis on Institutional Quality, Fiscal Policy and Debt Sustainability in Sub-Saharan Africa (SSA) - Onyele, Kingsley; Onyekachi-Onyele, Charity; Ikwuagwu, Eberechi B. (Center for Risk Management & Sustainability and RSF Press, 2024)
Many Sub-Saharan African (SSA) countries are finding it difficult to fulfill their massive debt repayment obligations, which bilateral financial institutions have declared to be unmanageable. Government institutions are to blame for such disparities in the budgetary components, which have been empirically confirmed to be detrimental. Part of the reason for SSA's income generation and debt management problems is related to fiscal policy components where there has been an unwarranted exaggeration of government expenditure. Accordingly, the current study used a panel Autoregressive Distributed Lag (ARDL) to examine how fiscal policy and institutional quality affected the sustainability of debt in 48 SSA nations between 2008 and 2022. The study’s findings suggested that the elements of fiscal policy (expenditure and revenue) as well as indicators of institutional quality (governance), such as control of corruption, effectiveness of government, political stability, absence of violence, regulatory quality, the rule of law, voice, and accountability, were important in explaining the long-term sustainability of public debt. The speed of adjustment to the long-run equilibrium was slow, which may be related to the unstable governance in each of the cross-sectional nations. Hence, the study concluded that the interactive effects of institutional quality and fiscal policy significantly influenced debt sustainability in the long run. The study’s conclusions can be very helpful to policymakers, particularly in those nations where major fiscal and external imbalances are being generated by low ratings for key institutional quality indices.